The Impact of Total Quality Management on Digital Projects in the Kingdom of Saudi Arabia (The International Journal for Scientific Research, 2024)
The main objective of this study is to investigate the Impact of applying Total Quality Management (TQM) principles on the success of digital projects in the Kingdom of Saudi Arabia. The study aims to understand how TQM contributes to achieving the goals of digital projects and improving their performance. The study used a descriptive analytical approach, and a questionnaire was used as a tool to collect information. The results indicate the importance of applying TQM principles in digital projects and provide guidance on areas that may need more attention to improve the quality of digital products and services. The study showed a strong positive Impact: the application of TQM principles has a strong positive impact on the quality of digital products and services (R = 0.823, R² = 0.677). The recommendations highlighted the need to: Strengthen the quality culture: InstitutIons in the Kingdom of Saudi Arabia should adopt a TQM culture in their digital projects, with a focus on improving decision-making processes. Also, to invest in skill development: Allocate sufficient resources to develop the skills of work teams in the field of digital technologies and quality management.
Keywords: Total Quality Management; Project Management; Digital Projects; Saudi Arabia